2018
DOI: 10.1097/fbp.0000000000000432
|View full text |Cite
|
Sign up to set email alerts
|

Executive (dys)function after stroke: special considerations for behavioral pharmacology

Abstract: Stroke is a worldwide leading cause of death and long-term disability with concurrent secondary consequences that are largely comprised of mood dysfunction, as well as sensory, motor, and cognitive deficits. This review focuses on the cognitive deficits associated with stroke specific to executive dysfunction (including decision making, working memory, and cognitive flexibility) in humans, nonhuman primates, and additional animal models. Further, we review some of the cellular and molecular underpinnings of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 172 publications
1
33
0
Order By: Relevance
“…With respect to concentration deficits [ 33 ]and fatigue [ 34 ] especially for stroke patients suffering from dysphagia (and aphasia), a shortened questionnaire comprising the factors with best loadings (bold items in Table 4 ) may be more useful after intensive reevaluation of the tool itself and a possible reliability–validity dilemma in other populations.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to concentration deficits [ 33 ]and fatigue [ 34 ] especially for stroke patients suffering from dysphagia (and aphasia), a shortened questionnaire comprising the factors with best loadings (bold items in Table 4 ) may be more useful after intensive reevaluation of the tool itself and a possible reliability–validity dilemma in other populations.…”
Section: Discussionmentioning
confidence: 99%
“…Proactive control in AX-CPT was reported to be relied upon the anticipation and prevention of interference before it occurred in the working memory (Braver, 2012;Ryman et al, 2019). Several studies have indicated working memory de cits in patients with stroke (Povroznik, Ozga, Vonder Haar, & Engler-Chiurazzi, 2018;van Geldorp, Kessels, & Hendriks, 2013). In the study by van Geldorp et al (2013), the participants were required to remember which cue was presented after a short temporal delay in a computerized delayed-match-to-sample task which included spatial, object, or binding (spatial + object) cues.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis showed that a program combining aerobic and resistance exercise (i.e., performed at moderate intensity, three times a week for 20 weeks) had a greater effect on cardiorespiratory fitness, muscle strength, and walking ability in stroke patients ( Lee and Stone, 2020 ) than aerobic or resistance training alone. However, this effect of exercise on cardiorespiratory fitness is not related to executive functions, which are dysfunctional in 75% of stroke patients ( Povroznik et al, 2018 ). Hence, future studies may explore the links between executive functions, cardiorespiratory fitness and cerebral oxygenation in stroke patients and even in other populations suffering from other chronic pathologies using a randomized controlled protocol.…”
Section: Futures Perspectives Of Researchmentioning
confidence: 99%